Study on Medical Equipment Management Program (MEMP) and its Preventive Maintenance: Optimizing Medical Equipment Management through Preventive Maintenance (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The approach of quality management of medical equipment based on key performanceindicators (KPIs) could be employed to quantify all elements of MEMS. It was also agreed that the plan formanaging medical equipment in public hospitals in an integrated and comprehensive way should beauthorized, as long as it is based on a conceptual framework with four domains of input, process,output, and result. . The degree of correlation between the four domains of the MEMS framework rangedfrom a moderate to a high level. The underperformance of one domain has a ripple effect on theperformance of other domains as well. The linear regression model confirmed that there was astatistically significant relationship between overall KPI scores and the usage coefficients of the medicalequipment under investigation.. The percentage completion of planned preventive maintenance (PPM)was found to be the most statistically significant predictor of UC among the four variables studied(Preventive maintenance, Accuracy and Quality Control, Corrective Maintenance, and Percentagecompletion of planned preventive maintenance).